Explosion loading on equipment from CFD simulations. (November 2016) - Hansen, Olav R.; Kjellander, Malte T.; Pappas, Jan A.
Abstract: Explosion studies using computational fluid dynamics (CFD) are performed on daily basis among safety consultants all over the world. The purpose of the explosion studies is usually to give guidance on required design strength of equipment, piping, blast walls or buildings. One key element is to translate the results from an explosion simulation, into actual forces on equipment. Major weaknesses exist in the current approaches for estimation of loads on small and medium sized equipment. In a previous work we demonstrated how loads on rectangular equipment could be estimated by combining free field form drag and pressure gradient. In the current work it is discussed how best to estimate loads onto other types of equipment including cylindrical pipes, pipe bundles and other shapes, and some comparisons and validation against large scale experiments are also included. The main findings of this work are the more accurate guidance on how best to extract explosion loads from simulations, including discussions on appropriate drag coefficients. Highlights: Explosion loading onto small, medium and large equipment walls and decks discussed. Improved methods to estimate received loading from simulated explosions proposed. Proper drag coefficient evaluated based on comparison with large scale test.